2019
DOI: 10.18406/2316-1817v11n220191299
|View full text |Cite
|
Sign up to set email alerts
|

Description of the carbon mineralization of swine manure and oat straw in the soil through nonlinear models

Abstract: Agricultural management is a viable way for recycling animal residues in feedlots. Thesubstances that make up organic residues change the dynamics of the organic matter decompositionin the soil. Information on carbon mineralization curves allows seeking improvements in soil qualityand, consequently, in crop productivity. The Stanford & Smith Nonlinear Model is the most usedto describe C mineralization of organic residues in the soil. This model considers organic residuesare composed of substances that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…The independence of errors was rejected for this treatment because the measurements were made in the same experimental unit, so the parameter ϕ was added to explain this correlation (TABLE 3), that is, for this treatment an adjustment with first-order auto-regressive error AR (1). Silva et al (2019a), Silva et al (2019b), and Hess and Schmidt (1995) also observed a correlation in errors when fitting nonlinear models to cumulative data of CO 2 mineralization of various organic residues in the soil. Estimates of parameters of the Stanford and Smith model and the half-life (t 1/2 ) with their respective 95% confidence intervals are listed in Table 2.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The independence of errors was rejected for this treatment because the measurements were made in the same experimental unit, so the parameter ϕ was added to explain this correlation (TABLE 3), that is, for this treatment an adjustment with first-order auto-regressive error AR (1). Silva et al (2019a), Silva et al (2019b), and Hess and Schmidt (1995) also observed a correlation in errors when fitting nonlinear models to cumulative data of CO 2 mineralization of various organic residues in the soil. Estimates of parameters of the Stanford and Smith model and the half-life (t 1/2 ) with their respective 95% confidence intervals are listed in Table 2.…”
Section: Resultsmentioning
confidence: 80%
“…In fitting the Molina model (double exponential) to C mineralization data from soil under eucalyptus plantation, Barreto et al (2010) obtained non-significant parameters for the model, thus indicating that the process did not have two carbon compartments. On the other hand, Silva et al (2019a) reported two phases of carbon mineralization of the treatments soil + oat straw, soil + pig slurry, and soil + pig slurry + oat straw, in addition, Silva et al (2019b) observed the same behavior for soil + sewage sludge + oat straw. indicated that for all treatments and both models the errors were independent (p-value > 0.05), except for the Juma model fit to the Acacia soil treatment (p-value < 0.05).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…É um modelo com dois parâmetros que representam o carbono potencialmente mineralizável e a constante de mineralização. O modelo Cabrera tem apresentado bons ajustes em processos que apresentam duas fases de mineralização, uma facilmente mineralizável com comportamento exponencial e outra resistente com comportamento constante (PAULA et al, 2020;PEREIRA et al, 2009;SILVA et al, 2020a;SILVA et al, 2019a;SILVA et al, 2019b;ZEVIANI et al, 2012). Outro modelo utilizado é o não linear Juma (PAULA et al, 2019;PEREIRA et al, 2005), com dois parâmetros que apresentam interpretação prática direta, carbono potencialmente mineralizável e tempo de meia-vida, respectivamente.…”
Section: Introductionunclassified